FEASIBILITY ANALYSIS OF LAYER CHICKEN FARMING: A CASE STUDY AT A LIVESTOCK BREEDING UNIT - Adinda Safitri; Ana Zuraida; Ilhamiyah Ilhamiyah (AL-ULUM: JURNAL SAINS DAN TEKNOLOGI, 2025)
This study was conducted over one year of production in 2024 to evaluate the feasibility of a layer chicken farming enterprise. The research employed a survey method with a case study approach, supported by descriptive and financial analyses. The financial assessment utilized the Revenue-Cost (R/C) Ratio to determine total costs, revenues, profits, and overall business viability. Results revealed that the enterprise incurred a total annual cost of IDR. 193,466,071, while generating revenues of IDR. 225,900,000. Consequently, the net profit amounted to IDR. 32,433,929 per year. The calculated R/C Ratio was 1.16, exceeding the threshold of 1.0, which indicates that the business is financially feasible and profitable. These findings suggest that the enterprise can be sustained and potentially expanded, as the profitability ratio demonstrates economic viability. The study contributes to the understanding of financial performance in layer chicken farming and provides a reference for similar agribusiness ventures.